TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN DALAM KELOMPOK USAHA BERSAMA (KUB) DI KELURAHAN RAWA MAKMUR KECAMATAN PALARAN KOTA SAMARINDA - Rahman, Fathur; Fitriyana, Fitriyana; Fahrizal, Wahyu (Bussman Journal : Indonesian Journal of Business and Management, 2025)
The purpose of this study is to determine the level of welfare of the fishing community in Rawa Makmur Village, Palaran District, Samarinda City based on the Fishermen’s Exchange Rate (NTN) indicator. This study lasted for 3 months, starting from December 2024 to February 2025. The sampling method applied Purposive Sampling and the Slovin technique with 20 respondents. The data analysis method applied was an analysis of the level of welfare. The results show that the calculation of NTN on the total income of fishermen’s households is 1.82 in 2024 and 1.75 in 2023. Then the NTN on fisheries income in 2024 was 1.74 and in 2023 was 1.67. Based on these indicators, the standard of living of fishermen in Rawa Makmur Village, Palaran District, Samarinda City can be said to be good or high and can be said to be prosperous. The Fishermen’s Terms of Trade Index (INTN) based on total income increased by 4.05%, indicating an improvement in purchasing power compared to the previous year. Meanwhile, the INTN based on total fisheries income also rose by 4.37%, This reflects a more favorable trade condition for fishermen, as the growth in the prices of their catch outpaced the rise in the cost of goods and services required for their livelihood